Strategi Komunikasi Penyuluh Agama Hindu Kabupaten Bulengleng pada Masa New Normal - Niluh Wiwik Eka Putri; I Gede Titah Pratyaksa; Komang Agus Widiantara (Universitas Merdeka Malang, 2022)
The Hindu Religious Counselor in Buleleng Regency coordinated by the Buleleng Regency Ministry of Religion has an important role in providing spiritual guidance to the Buleleng community. The right communication strategy is needed so that the messages conveyed can hit the hearts of the people so that the various problems above can be handled properly. This study uses a qualitative method and a phenomenological approach. In carrying out Hindu religious counseling, the Buleleng Regency Hindu instructor carries out communication planning which includes Analysis of Audience and Community Needs of Buleleng Regency, Determination of Communication Targets, message design, channels, and recipients, Implementation of planning that includes funds, human resources, and time. The communication strategies of Hindu Religious Instructors used in the New Normal Period include Intrapersonal Communications for Hindu Religion Instructors, Interpersonal Communications for Hindu Religion Instructors, Group Communications for Hindu Religious Instructors, Mass Communication for Hindu Religion InstructorsKeywords: Communication Strategy, Hindu Religion Counselor, Buleleng, New Normal